Lichens from the Utsteinen Nunatak (Sør Rondane Mountains, Antarctica), with the description of one new species and the establishment of permanent plots - Ertz, Damien; Aptroot, André; van De Vijver, Bart; Sliwa, Lucyna; Moermans, Coraline; Øvstedal, Dag (Phytotaxa, 2014)
In order to establish baseline environmental conditions at the Utsteinen Nunatak (Sør Rondane Mountains, Antarctica) chosen for the installation of the new Belgian Antarctic research station, a detailed survey of the different lichen species was performed in 2007. The establishment of permanent plots will allow the accurate monitoring of possible future impacts of human activities on the biodiversity and, on a long-term scale, to detect future climate changes. A complete survey of the lichen species was made for each of the 23 permanent plots of the Utsteinen Ridge. The abundance of each species within each plot was also evaluated. Exhaustive lists of lichens were also completed for other parts of the Utsteinen Nunatak. Additionally, historic collections from the same area were revised. A total of twenty-three lichen species and two lichenicolous fungi was detected in the recent samples whereas the historic material yielded three additional species. These results raise the total number of known taxa for the Sør Rondane Mountains from ten to 28, despite the small area investigated. Trapelia antarctica is described as new to science. Buellia bastini is synonymized with Buellia nelsonii and Lecidea autenboeri is synonymized with Carbonea vorticosa. The lichen flora of Utsteinen is made of a high percentage (48%) of Antarctic endemics. Lichens were abundantly present on the Utsteinen Ridge. The numbers of species per plot varied from one to 18 with an average of ten. The detailed grid map for the Utsteinen Ridge will be useful in monitoring future changes in lichen population and diversity. Five plots presented the richest lichen flora and need therefore careful protection against any future human activities.